Penilaian Kesesuaian Aktivitas Pengunjung Kawasan Sport Center Kudus dengan Metode Skoring - Ferdizza Yaurma Hanatya; Landung Esariti (Jurusan Perencanaan Wilayah dan Kota, 2019)
There are various kinds of problems in the Kudus Sport Center area, such as ldan conflicts by street vendors dan criminal acts such as theft. Based on these problems there is a mismatch of visitor activity that takes place in the region. This study aims to assess the suitability of visitor activities in utilizing the Kudus Sport Center area. The analysis used was descriptive analysis dan scoring with 5 variables which were reduced to 18 assessment indicators. These variables are ease of accessibility to the area, availability of facilities, condition of facilities, security, dan activities that take place in the Kudus Sport Center area. Data used from the results of the questionnaire to 90 respondents, interviews, dan observations. The results of this study are the appraisal of the suitability of the activities of the Kudus Sport Center area of 67.56% which is included in the medium category, so that there are still assessment indicators that have not been applied in the area. The indicator according to the priority of its handling is that it can be reached by public transportation dan sports dan recreation facilities that are free from garbage dan standing water.